PROBLEMATIC SCHOOL THEATER: INTERPRETING AESTHETICS AND PEDAGOGY - Indra Suherjanto (Jurusan Sastra Indonesia, 2017)
The phenomenon of school theater if classified includes the following issues: 1) the resources of teachers and coaches who are not all art education backgrounds, and understand the concepts of theater and theater (dramaturgy, acting techniques, and directing methods, 2) still a negative perception of school theater 3) goodwill and school interpretation of the purpose and benefits of school theater (just perform, practice community or human character building). The school theater is a form of activity that produces beauty with novelty in the work of the show. The work of theater performances in question is the artwork that berdramaturgi as a 'theater process'. Theaterpedagogy is interpreted as a theater education, educational process, and theater learning process. A process of changing the attitude and conduct of a person or group of people in an effort to mature human beings through the efforts of teaching and training; processes, ways, and deeds educate with, through / and use the art of theater. To solve the problem of school theater required renewal of the method in running the school theater based on aesthetic thinking and pedagogy.